2004
DOI: 10.1159/000076998
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Glycoprotein IIb/IIIa Receptor Inhibition with Tirofiban on Minor Myocardial Damage in Angiographically Successful Percutaneous Coronary Angioplasty

Abstract: Aim: The aim of the study was to evaluate the effects of glycoprotein (GP) IIb/IIIa inhibition on minor myocardial injury characterized by cardiac troponin I (cTn-I) and cardiac troponin T (cTn-T) elevation after elective successful percutaneous coronary intervention (PCI). Methods: The study consisted of 119 consecutive patients scheduled for elective coronary balloon angioplasty with or without stent implantation. Sixty-three patients (mean age 58 ± 9.4 years) were randomized to receive standard therapy, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…Safety. Major bleeding was reported in all but 7 trials (27)(28)(29)(30)(32)(33)(34). The incidence of major bleeding was 1.2% with GPI versus 0.9% with control (RR: 1.37, 95% CI: 0.83 to 2.25, p ϭ 0.22) (Fig.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Safety. Major bleeding was reported in all but 7 trials (27)(28)(29)(30)(32)(33)(34). The incidence of major bleeding was 1.2% with GPI versus 0.9% with control (RR: 1.37, 95% CI: 0.83 to 2.25, p ϭ 0.22) (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Our search identified 22 studies with 10,123 patients (Fig. 1, Table 1) (10,11,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). The studies examined a variety of clinical outcomes, including 7 that used a nonclinical primary outcome (Table 2) (23,24,26,27,30,32,34).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that 74% of patients with aspirin and clopidogrel pretreatment show have troponin T levels 48 h after successful PCI . In patients pretreated with aspirin and clopidogrel, pretreatment with tirofiban was associated with early reinforced antiplatelet effects and the prevention of platelet thrombus formation, which consequently improved the myocardial blood supply and attenuated minor myocardial damage among NSTE‐ACS patients undergoing PCI . The EVEREST trial and a trial in China also showed that routine pretreatment with tirofiban significantly improves TIMI flow before PCI and reduces myocardial damage .…”
Section: Discussionmentioning
confidence: 98%
“…In ARMYDA, atorvastatin reduced the release of CK-MB, troponin, and myoglobin compared with placebo. 15 Intracoronary propranolol, 21 celecoxib, 20 glycoprotein IIb/IIIa inhibitors, 18 and pyridoxal-5Ј-phosphate monohydrate 17 all reduced myocardial damage after PCI.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size of previous studies 15,[17][18][19][20][21] testing interventions to reduce markers after elective PCI has ranged from 50 to 153 (mean, 105). The sample size used in ARMYDA was 153.…”
Section: Sample Size Considerationsmentioning
confidence: 99%